2021
DOI: 10.1038/s41467-021-23706-8
|View full text |Cite
|
Sign up to set email alerts
|

Lasp1 regulates adherens junction dynamics and fibroblast transformation in destructive arthritis

Abstract: The LIM and SH3 domain protein 1 (Lasp1) was originally cloned from metastatic breast cancer and characterised as an adaptor molecule associated with tumourigenesis and cancer cell invasion. However, the regulation of Lasp1 and its function in the aggressive transformation of cells is unclear. Here we use integrative epigenomic profiling of invasive fibroblast-like synoviocytes (FLS) from patients with rheumatoid arthritis (RA) and from mouse models of the disease, to identify Lasp1 as an epigenomically co-mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 49 publications
1
25
0
Order By: Relevance
“…This identified a gene signature panel representing an interactive biological network of hub (STAT1, RAC2 and KYNU) proteins and effector molecules (PEPD receptor and NR4A1, MEOX2, KLF4, IRF1 and MYB transcription factors and miRs-146a, -299, -3659, -6882 and -8078) that provides a platform for validation of pathogenic mechanisms and potentially, a predictive tool for diagnosis and development of effective treatment strategies for RA: apart from KYNU and miR-299 (miRs-3659, -6882 and -8078 were not identified in our methylome study), our proof-of-concept methylome analysis suggests that these “signature” genes may be differentially methylated in naïve-, CIA- and ES-62-CIA-SFs. Likewise, very recently [ 82 ], an integrated epigenetic study (histone marks, open chromatin, transcriptomics and DNA methylation) identified 8 epigenetic clusters that differentially modified in healthy and hyper-responsive SFs (from both humans and mouse models). Although different mouse models to CIA (hTNFtg and G6PI-induced arthritis models) were analysed, essentially all of the 52 genes exhibiting differential DNA methylation, and clustered on the basis of their involvement in the proliferation, migration and cell-cell interaction processes involved in the pathogenic transformation of RA SFs, appeared to be differentially methylated amongst our Naïve, CIA and CIA-ES-62 groups, albeit in some cases these changes were subtle and all require statistical validation.…”
Section: Discussionmentioning
confidence: 99%
“…This identified a gene signature panel representing an interactive biological network of hub (STAT1, RAC2 and KYNU) proteins and effector molecules (PEPD receptor and NR4A1, MEOX2, KLF4, IRF1 and MYB transcription factors and miRs-146a, -299, -3659, -6882 and -8078) that provides a platform for validation of pathogenic mechanisms and potentially, a predictive tool for diagnosis and development of effective treatment strategies for RA: apart from KYNU and miR-299 (miRs-3659, -6882 and -8078 were not identified in our methylome study), our proof-of-concept methylome analysis suggests that these “signature” genes may be differentially methylated in naïve-, CIA- and ES-62-CIA-SFs. Likewise, very recently [ 82 ], an integrated epigenetic study (histone marks, open chromatin, transcriptomics and DNA methylation) identified 8 epigenetic clusters that differentially modified in healthy and hyper-responsive SFs (from both humans and mouse models). Although different mouse models to CIA (hTNFtg and G6PI-induced arthritis models) were analysed, essentially all of the 52 genes exhibiting differential DNA methylation, and clustered on the basis of their involvement in the proliferation, migration and cell-cell interaction processes involved in the pathogenic transformation of RA SFs, appeared to be differentially methylated amongst our Naïve, CIA and CIA-ES-62 groups, albeit in some cases these changes were subtle and all require statistical validation.…”
Section: Discussionmentioning
confidence: 99%
“…However, the treatment with a humanized monoclonal antibody against cadherin-11 (RG6125) failed to show efficacy in patients with RA inadequately responding to anti-TNFα therapy in a phase 2 clinical trial and led to the withdrawal of this synovial fibroblast-selective intervention from the list of potential future therapies of RA 75. Meanwhile, in a recent article, the LIM and SH3 domain protein 1 (Lasp1) was found to be upregulated in the RA synovium and was described as an important mediator of the cell responses (eg, migration) of arthritic FLS 5. Further studies revealed that the loss of Lasp1 resulted in abrogated cadherin-11-containing cell-cell contacts and decreased the severity of experimental arthritis in mice, pointing at its target potential in the therapy of RA 5…”
Section: Blocking Cellular and Cell-matrix Interactions Of Synovial F...mentioning
confidence: 99%
“…Meanwhile, in a recent article, the LIM and SH3 domain protein 1 (Lasp1) was found to be upregulated in the RA synovium and was described as an important mediator of the cell responses (eg, migration) of arthritic FLS 5. Further studies revealed that the loss of Lasp1 resulted in abrogated cadherin-11-containing cell-cell contacts and decreased the severity of experimental arthritis in mice, pointing at its target potential in the therapy of RA 5…”
Section: Blocking Cellular and Cell-matrix Interactions Of Synovial F...mentioning
confidence: 99%
See 2 more Smart Citations